2009
DOI: 10.1038/cgt.2009.15
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of Belagenpumatucel-L, a TGF-β2 antisense gene modified allogeneic tumor vaccine in advanced non small cell lung cancer (NSCLC) patients

Abstract: In a previous dose escalation trial we demonstrated dose related survival correlation to Belagenpumatucel-L. In order to further evaluate safety and response at the previously defined optimal dose and schedule and to gain preliminary evidence on a hypothesis that the level of circulating tumor cells (CTCs) in blood may correlate with the overall survival of patients with stage IV NSCLC, we initiated a phase II trial. Patients received intradermal immunization of 2.5 Â 10 7 transfected allogeneic tumor cells (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(64 citation statements)
references
References 32 publications
0
64
0
Order By: Relevance
“…When injected into the patient, Lucanix promotes an antihost NSCLC cytotoxic T cell response, and vaccine immunogenicity is postulated to be potentiated by reduced TGF-b2 production. Phase I and II trials went well, the drug was found to be safe, and the phase II results suggested some therapeutic benefit (Nemunaitis et al , 2009. However, a phase III trial to examine benefit as a NSCLC maintenance therapy following primary treatment (270 Lucanix-treated vs. 262 placebo-treated NSCLC patients) did not meet its primary endpoint criterion of increased overall survival (OS) (Giaccone et al 2015).…”
Section: Update On Interventional Clinical Oncology Trials With Tgf-bmentioning
confidence: 99%
“…When injected into the patient, Lucanix promotes an antihost NSCLC cytotoxic T cell response, and vaccine immunogenicity is postulated to be potentiated by reduced TGF-b2 production. Phase I and II trials went well, the drug was found to be safe, and the phase II results suggested some therapeutic benefit (Nemunaitis et al , 2009. However, a phase III trial to examine benefit as a NSCLC maintenance therapy following primary treatment (270 Lucanix-treated vs. 262 placebo-treated NSCLC patients) did not meet its primary endpoint criterion of increased overall survival (OS) (Giaccone et al 2015).…”
Section: Update On Interventional Clinical Oncology Trials With Tgf-bmentioning
confidence: 99%
“…The relevance of TGF-b signaling for disease progression has been particularly recognized in tumors where cancer cells retain the core TGF-b signaling components, as is often the case in breast and lung cancers (Kang et al 2003;Elliott and Blobe 2005;Massague 2008;Padua and Massague 2009). Indeed, in lung adenocarcinoma (ADC), the most common subtype of lung cancer with a high mortality rate, increased TGF-b1 expression correlates with tumor progression and poor patient survival, and various experimental model systems support a prometastatic role for TGF-b in these tumors (Lund et al 1991;Hoffman et al 2000;Hasegawa et al 2001;Gibbons et al 2009;Nemunaitis et al 2009;Toonkel et al 2010;Provencio et al 2011;Vazquez et al 2013). However, a major remaining challenge is the identification of TGF-b target genes that drive the different steps of metastasis, especially since TGF-b modulates gene expression in a highly cell-and context-specific manner (Padua and Massague 2009;Mullen et al 2011;Massague 2012).…”
mentioning
confidence: 99%
“…Therefore, TGFß1 expression is an indicator of the aggressiveness or malignancy of solid cancers. Consequently, various molecular targeting therapies for TGFß1 and its receptors are being investigated (20)(21)(22), and some have already been introduced clinically (23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%